Difficulties in diagnosis of bovine tuberculosis in suggestive lesions on post-mortem inspection in carcasses - Siconelli, Márcio Junio Lima [UNESP]; Vey-da-Silva, David Attuy; De Souza-Pollo, Andressa [UNESP]; Bürger, Karina Paes [UNESP] (Revista Brasileira de Medicina Veterinaria, 2018)
The bovine tuberculosis is a zoonotic disease with importance to the public health. The post-mortem identification and its fast and accurate diagnosis combined with the epidemiology knowledge are essential to fight against the spread of the disease. Therefore, we aimed to perform the identification of Mycobacterium bovis DNA, the histopathologic characterization of the affected lymph nodes and the detection of acid-fast bacilli (AFB), seeking to compare them. During slaughter of cattle in slaughter plants, under Federal Inspection Service in São Paulo State, lymph nodes with tuberculosis-like lesions were collected and labeled in duplicate. One was intended to the histopathology characterization (hematoxylin-eosin – HE, staining for lesion characterization and the Ziehl-Neelsen – ZN, staining to detect the AFB). The other sample was separated to the M. bovis DNA identification by Polymerase Chain Reaction (PCR) and nested PCR. The bacterial DNA could be identified in 20.84% (10/48) of the collected lymph nodes. However, when the results were compared with more sensitive tests (nested PCR) and cheapest ones (histopathological characterization of lesions by HE and the AFB detection by ZN), different results were found. When performing nested PCR technique was applied in PCR negative samples (38/48), it was found 18.74% (9/38) more positive samples results. Thus, we could identify the M. bovis DNA in 39.58% (19/48) of the collected lymph nodes. However, applying the HE staining we characterize 66.67% (32/48) of the samples as tuberculosis-like lesions and ZN staining detected 54.17% (26/48) of AFB. A multi-step approach involving diferents testa, molecular and histopathological, can help to identify M. bovis in tissues, like lymph nodes, from naturally infected bovines and allows a broader epidemiological approach.
Keywords: Cattle; M. bovis; PCR; Zoonosis